Emerging therapeutic frontiers in hypertension management - Diana-Ligia Pena; Justin Aurelian; Mihai Grigore; Andreea-Simona Hodorogea; Emma Weiss; Elisabeta Bădilă; Adriana-Mihaela Ilieșiu; Ana-Maria Balahura (Frontiers in Cardiovascular Medicine)
Resistant hypertension, characterized by persistently elevated blood pressure despite adherence to multiple antihypertensive therapies, remains a significant global health challenge. This condition is associated with increased cardiovascular morbidity and mortality, highlighting the urgent need for more effective treatment strategies. While current management focuses on lifestyle modification and pharmacotherapy, many patients do not achieve target blood pressure levels. Recent advances have led to the development of emerging therapies targeting novel mechanisms, including gene silencing, receptor modulation, enzyme inhibition, and immunomodulation. This descriptive review examines the efficacy, safety, and clinical trial progress of these innovative therapeutic approaches, offering new hope for improved blood pressure control in resistant hypertension.